2
$\begingroup$

Let $x,y,z$ be nonnegative real numbers such that $x+z\leq2$

Prove that, and determine when equality holds.

$(x−2y+z)^2 \geq 4xz−8y$

Please correct me if my methods are incorrect or would lead nowhere.

I tried expanding the LHS of the inequality getting

$x^2+4y^2+z^2-4xy-4yz+2xz \geq 4xz-8y$

And got lost as to how I should manipulate the inequality to find something true through rough work.

After I tried manipulating

$x+z\leq2$ subtract 2

$x+z-2\leq0$ since $y\ge 0$

$x+z-2\le y$ subtract 2y and add 2 to both sides

$x-2y+z\le 2-y$

And again lost sight of how I could manipulate the inequalities.

$\endgroup$
2
$\begingroup$

Note that $y\geq 0$ and $x+z\leq 2$ imply $$(x-2y+z)^2+8y\geq (x-2y+z)^2+4(x+z)y=x^2+4y^2+z^2+2xz\,.$$ Thus, $$(x-2y+z)^2+8y\geq (x-z)^2+4y^2+4xz\geq 4xz\,,$$ whence $$(x-2y+z)^2\geq 4xz-8y\,.$$ The equality holds if and only if $(x,y,z)=(t,0,t)$ for some $t\in[0,1]$.

$\endgroup$
1
$\begingroup$

Because $$(x-2y+z)^2+8y-4xz\geq(x-2y+z)^2+4y(x+z)-4xz=$$ $$=x^2+4y^2+z^2-2xz=(x-z)^2+4y^2\geq0.$$ The equality occurs for $y=0$,$x=z\geq0$ and $x+z\leq2$.

$\endgroup$
0
$\begingroup$

consider,

$(x-2y+z)^2-4xz+8y=x^2+4y^2+z^2-4xy-4yz+2xz-4xz+8y$ $=x^2+4y^2+z^2-4xy-4yz-2xz+8y=x^2+4y^2+z^2-4y(x+z)-2xz+8y$ $=(x-z)^2+4y^2+4y(2-(x+z))\geq 0$

because $y$ is non negative and $x+z\leq 2$. Hence that inequality holds.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.